👤

(-2+5)*(-3)=
(-3-8)*(8-12)=
(5-(-2))*(3-(-6))=
4-(-6)/-2=
(-13-8):(-3+10)=
(-3)*(2-7)-(-6+2)=
(13-18)-(17-(-3))/10-15=
-2*(-3)-4*(-7)/7-9=
oblicz:​


Odpowiedź :

Odpowiedź:

[tex]( - 2 + 5) \times ( - 3) = 3 \times ( - 3) = - 9[/tex]

[tex]( - 3 - 8) \times (8 - 12) = - 11 \times ( - 4) = 44[/tex]

[tex](5 - ( - 2)) \times (3 - ( - 6)) = 7 \times 9 = 63[/tex]

[tex]4 - ( - 6) \div ( - 2) = 10 \div ( - 2) = - 5[/tex]

[tex]( - 13 - 8) \div ( - 3 + 10) = - 21 \div 7 = - 3[/tex]

[tex]( - 3) \times (2 - 7) - ( - 6 + 2) = - 3 \times ( - 5) + 4 = 15 + 4 = 19[/tex]

[tex](13 - 18) - (17 - ( - 3)) \div 10 - 5 = - 5 - 20 \div 10 - 5 = - 5 - 2 - 5 = - 12[/tex]

[tex] - 2 \times ( - 3) - 4 \times ( - 7) \div 7 - 9 = 6 + 4 - 9 = 1[/tex]